Deep structure and evolution of the Harz Mountains: results of three-dimensional gravity and finite-element modeling - Gabriel, G.; Jahr, T.; Jentzsch, G.; Melzer, J. (Tectonophysics, 1997)
A new Bouguer anomaly map is presented for the region of the entire Harz Mountains based on more than 60,000 gravity values. The various gravity anomalies are discussed and interpretation is carried out by high-resolution 3-D gravity modeling. One of the main subjects of interest in the investigation is the northern boundary fault zone of the Harz Mountains, separating the Mesozoic sediments in the north from the Palaeozoic rocks of the Harz in the south. Dip and vertical displacement are determined for this fault zone; mean values are 3400 m and 70°, respectively. Gravity modeling shows that the Brocken and the Ramberg Granites are distinctly different. The Brocken Granite is shallow, whereas the Ramberg Granite has a maximum depth of 8.5 km and a NS dimension of 37 km. The prominent Benneckenstein Gravity High is explained by two different models, one based on a granodioritic intrusion (2900 kg/m 3) with a center-depth of 14 km and the other based on phyllites (2740 kg/m 3) on a depth of 3–4 km. Studies on the geodynamic evolution of the Harz Mountains are carried out using the finite-element method. On the basis of a 3-D model, vertical displacements that can be related to horizontal forces are computed. For the period of the Variscan Orogeny an uplift of 600 m in the Harz area is calculated, for Late Cretaceous and Tertiary 400 m are determined. The total amount of 1000 m is about 1 2 of the vertical displacement of the northern boundary fault zone of the Harz Mountains shown by the gravity modeling. These results do not contradict geological ideas.